Desialylation is associated with apoptosis and phagocytosis of platelets in patients with prolonged isolated thrombocytopenia after allo-HSCT. Issue 1 (December 2015) - Zhang, Xiao-Hui; Wang, Qian-Ming; Zhang, Jia-Min; Feng, Fei-Er; Wang, Feng-Rong; Chen, Huan; Zhang, Yuan-Yuan; Chen, Yu-Hong; Han, Wei; Xu, Lan-Ping; Liu, Kai-Yan; Huang, Xiao-Jun
Abstract Background Prolonged isolated thrombocytopenia (PT) is a frequent complication in patients who undergo allogeneic hematopoietic stem cell transplantation (allo-HSCT), and it is associated with an adverse prognosis. In this study, we hypothesized that desialylation on platelet surfaces was associated with PT after allo-HSCT. The mechanisms participating in this process may include NEU1 translocation, platelet apoptosis, and phagocytosis by macrophages. Methods PT was defined as a peripheral platelet count less than 100 × 109 /L without sustained anemia or leukopenia for more than 3 months after allo-HSCT. 34 patients were identified consecutively from a cohort of 255 patients who underwent allo-HSCT for hematologic malignancies between May and October 2014 at Peking University Institute of Hematology. Desialylation, enzyme expression, and phagocytosis were detected using flow cytometry, immunofluorescence, RT-PCR, Western blot, and so on. Results Platelets from the PT patients had significantly fewer sialic acids (P  = .001) and increased β-galactose exposure indicative of desialylation on the surface (P  = .042), and serum from the PT patients showed a higher sialic acid concentration (8.400 ± 0.2209 μmol/L, P  < .001). The sialidase NEU1 was over-expressed from mRNA to protein levels, and its catalytic activity was increased in platelets from the PT patients. Desialylation of GPIbα in the PT patients was correlated with changes in 14-3-3ζ distribution, which, relative to Bad activation, modulated the expression of Bcl-2 family proteins, depolarized the inner membrane of the mitochondria, and initiated the intrinsic mitochondria-dependent pathway of apoptosis. Macrophages derived from the THP-1 cell line preferred to phagocytize desialylated platelets from the PT patients in vitro. We also revealed that oseltamivir (400 μmol/L) could inhibit 50 % of the sialidase activity on platelets and could protect 20 % of platelets from phagocytosis in vitro. Conclusions Desialylation of platelets was associated with platelet apoptosis and phagocytosis, whereas oseltamivir could reduce platelet destruction in the periphery, indicating a potential novel treatment for PT after allo-HSCT.